Caracterización sistemática de la colección de sapotaceas (Pouteria sapota (Jacq.) H. E. Moore & Stearn; Manilkara zapota (L.) P. van Royen y Chrysophyllum cainito L.) del CATIE - Gazel Filho, A.B. (1995)
Tesis (Mag.Sc.) - CATIE, Turrialba (Costa Rica),1995